From Living Qur'ān to Living Īmān: Syed Naquib al-Attas's Reception of Theological Verses and the Formulation of New Kalam - Cholid Ma'arif; Nadia Hanim Binte Abdul Rahman; Mohammad Kholid Muslih (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article examines Syed Muhammad Naquib al-Attas’ interpretation and application of Quranic verses as foundational principles for his conception of the Islamization of knowledge, primarily drawing from his work Islam: The Concept of Religion and the Foundation of Ethics and Morality. The study investigates how al-Attas’ theological reception of Quranic verses contributes to the development of kalam jadid (new kalam) within the context of knowledge Islamization. The research employs al-Attas’ interpretation of theological verses as its material object, while utilizing the framework of new kalam as its formal object. Through the Living Qur’an methodology, the study analyzes the significance of al-Attas’ engagement with theological verses throughout his scholarly corpus. This qualitative investigation combines observational and library research methods to present a systematic descriptive-analytical discussion. The findings are as follows: First, al-Attas employs at least 14 Quranic verses with theological reception as the basis for formulating new kalam, emphasizing three agendas—change, development, and progress—all rooted in divine principles, which frame the discourse of the Islamization of knowledge. Second, in terms of practical reception, al-Attas’ interpretations can be observed in the initiatives of one of his ideological successors in Indonesia, Hamid Fahmi Zarkasyi. These include institutionalizing his thought through the establishment of University of Darussalam (UNIDA), the Center for Islamic and Occidental Studies (CIOS), and Program Kaderisasi Ulama (PKU) or cleric cadre program. In the perspective of the Living Qur’an, these initiatives represent efforts to enliven the Quran beyond its textual tradition, extending into a civilizational thought of new kalam institutionalized for broader impact. This progression begins from Quranic abstraction and reception, leading to the formulation of new kalam, and further towards enlivening both the Quran and faith (iman) simultaneously. This study makes a significant contribution by integrating Syed Muhammad Naquib al-Attas’ theological thought with the concept of new kalam, relevant to the Islamization of knowledge. It expands the understanding of how Quranic theological texts can serve as a conceptual basis for advancing progressive Islamic intellectual discourse.